The Criminalisation of Children in the Juvenile Criminal Justice System: a Human Rights Protection Perspective - Rosinta Paulina Br Simatupang; Padrisan Jamba (Sean Institute, 2025)
Juvenile justice is a complex subject since it covers multiple interconnected topics, including law, justice, and the protection of children's rights. In Indonesia, the criminal justice system's approach to juvenile crimes has shifted from a focus on punishment for misconduct to one that prioritizes rehabilitation and reintegration into society. The purpose of this study is to examine the criminalisation of children in the juvenile criminal justice system, as outlined in Law No. 11 of 2012 on the Juvenile Criminal Justice System (SPPA Law), and to assess the extent to which the principle of human rights protection is applied. The methodology employed is normative legal analysis with a regulatory and conceptual focus. This study examines the applicable legal rules, the basic principles of child protection, and the theory of restorative justice that forms the basis of juvenile criminal justice. The results show that, in terms of regulations, the UU SPPA already provides protection for children through diversion mechanisms, restrictions on prison sentences, and the affirmation of children's rights in the judicial process. However, implementation in the field still faces several obstacles, such as a lack of understanding among legal officials, limited guidance facilities, and a lack of cooperation between institutions. This has resulted in the principle of human rights protection not being fully realised in the practice of juvenile punishment. Therefore, it is necessary to improve the application of restorative justice principles, enhance the capacity of juvenile justice institutions, and conduct continuous monitoring to ensure that the juvenile justice system is truly oriented towards the protection, rehabilitation, and fulfilment of children's rights in a comprehensive manner